2021
DOI: 10.1002/ange.202111265
|View full text |Cite
|
Sign up to set email alerts
|

Predesign of Catalytically Active Sites via Stable Coordination Cluster Model System for Electroreduction of CO2 to Ethylene

Abstract: Purposefully designing the well‐defined catalysts for the selective electroreduction of CO2 to C2H4 is an extremely important but challenging work. In this work, three crystalline trinuclear copper clusters (Cu3‐X, X=Cl−, Br−, NO3−) have been designed, containing three active Cu sites with the identical coordination environment and appropriate spatial distance, delivering high selectivity for the electrocatalytic reduction of CO2 to C2H4. The highest faradaic efficiency of Cu3‐X for CO2‐to‐C2H4 conversion can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Very recently, Lan and coworkers demonstrated that pyrazolate-bridged dicopper compounds (Scheme 1a) have ECR performances for yielding C 2+ products and show a Faradaic efficiency (FE) of ca. 60% under strong alkaline conditions, 20,31 though lower than those of the best Cu-based nanomaterials/nanocomposites (FE > 70%). 32,33 This might be ascribed to the higher Gibbs freeenergy barriers of hydrogenation of intermediates in ECR.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Very recently, Lan and coworkers demonstrated that pyrazolate-bridged dicopper compounds (Scheme 1a) have ECR performances for yielding C 2+ products and show a Faradaic efficiency (FE) of ca. 60% under strong alkaline conditions, 20,31 though lower than those of the best Cu-based nanomaterials/nanocomposites (FE > 70%). 32,33 This might be ascribed to the higher Gibbs freeenergy barriers of hydrogenation of intermediates in ECR.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Chemistry research has sought ‘green’ options that do not generate CO 2 , for both ammonia and hydrogen production [29–31], as well as methods by which CO 2 generated can be captured, either for long-term lock-in (e.g. as stable carbonates) or for use in other chemical and physical applications [32,33].…”
Section: How Does/can Chemistry Contribute To Resilience?mentioning
confidence: 99%